A nickel-iron-based metal alkoxide catalyst and its preparation method and application

By using nickel-iron-based metal alkoxide catalyst in the oxygen evolution reaction, the problems of low performance and strict preparation conditions of the existing catalyst are solved, and efficient catalytic performance of the oxygen evolution reaction and flexible preparation conditions are achieved, and energy consumption is reduced.

CN115896855BActive Publication Date: 2025-03-25HYDROGEN PAVILION TECHNOLOGY (SUZHOU) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211581947.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-08
Publication Date
2025-03-25
Estimated Expiration
2042-12-08

AI Technical Summary

Technical Problem

The existing nickel-iron-based metal alkoxide catalyst has low catalytic performance in oxygen evolution reaction and strict preparation conditions, which limits its large-scale application.

Method used

By dissolving the nickel salt and the iron salt in a mixed solution containing isopropanol, glycerin and deionized water, pouring it into a polytetrafluoroethylene liner and stirring, and then carrying out a hydrothermal reaction, a nickel iron-based metal alkoxide catalyst with a regular uniform morphology was prepared.

Benefits of technology

The preparation of nickel-iron-based metal alkoxide catalyst with different raw materials and nickel-iron ratios has excellent catalytic performance of oxygen evolution reaction, and the overpotential can be reduced to 215mV, reducing the energy consumption in the process of electrolyzing hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115896855B_ABST
    Figure CN115896855B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a nickel-iron-based metal alkoxide catalyst, comprising step one: dissolving a nickel salt and an iron salt in a first mixed solution comprising isopropanol, glycerol and deionized water to obtain a second mixed solution; step two: pouring the second mixed solution into a polytetrafluoroethylene liner and continuously stirring for 30 to 60 minutes; step three: transferring the polytetrafluoroethylene liner to a high-pressure reactor, reacting at 200°C for 12 hours and then cooling to room temperature to obtain a nickel-iron-based metal alkoxide catalyst. The method for preparing a nickel-iron-based metal alkoxide provided by the present invention can realize the preparation of a nickel-iron-based metal alkoxide catalyst with nanoscale regular and uniform morphology of different types of raw materials and different nickel-iron element ratios under the preparation condition of a hydrothermal reaction at 200°C for 12 hours, and the nickel-iron-based metal alkoxide has a current density of 10 mA / cm in an oxygen evolution reaction. 2 The overpotential can be reduced to 215mV, which can greatly reduce the energy consumption in the process of hydrogen production by water electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of oxygen evolution reaction catalysts, and in particular to a nickel-iron-based metal alkoxide catalyst and a preparation method and application thereof. Background Art

[0002] Energy has always been the driving force of global social and economic development, especially sustainable and clean energy has received more and more attention in recent years. Under the consensus of carbon neutrality, hydrogen energy, as a clean and renewable energy, is the core development object in the new round of energy transformation, and plays an important role in transportation, chemical industry, metallurgy and other fields. The key to the large-scale application of hydrogen energy lies in hydrogen-electricity conversion, and hydrogen production by water electrolysis is an effective strategy for large-scale green hydrogen production.

[0003] The oxygen evolution reaction (OER) is a bottleneck problem in the process of hydrogen production by water electrolysis because of its slow reaction kinetics and the need for high overpotential. Efficient catalysts can effectively accelerate this complex transformation process of multi-step proton coupling and electron transfer. Currently, commercial catalysts such as iridium dioxide and ruthenium dioxide can effectively accelerate the complex four-electron transfer process in OER, but the high price and scarcity of precious metals greatly inhibit the possibility of their large-scale application. Therefore, it is urgent to develop and utilize non-precious metal OER catalysts with both high activity and long stability.

[0004] So far, nickel-iron-based catalysts are the most effective and promising catalysts in alkaline OER. The two metal sites, nickel and iron, are like two "best partners" that can work together in many ways to produce excellent performance. Metal alkoxides, as a nanomaterial with organic-inorganic composite properties, have the characteristics of metal ionization and morphological diversity. However, the research and application of such materials in OER catalysts are still rare, and their catalytic performance is still far behind that of commercial catalysts. In particular, to obtain nickel-iron-based metal alkoxides with regular and uniform morphology and high catalytic activity, the synthesis conditions have very strict requirements in terms of raw material selection, nickel-iron element ratio, temperature and time, etc., which hinders the large-scale application of nickel-iron-based metal alkoxide catalysts. Summary of the invention

[0005] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide a controllable method for preparing nickel-iron-based metal alkoxides, which has a large space for selecting raw materials, the ratio of nickel and iron elements can be adjusted arbitrarily, and the morphology of the obtained nanomaterial is regular and uniform.

[0006] To achieve the above object, the present invention provides a method for preparing a nickel-iron-based metal alkoxide catalyst, comprising the following steps:

[0007] Step 1, dissolving nickel salt and iron salt in a first mixed solution comprising isopropanol, glycerol and deionized water to obtain a second mixed solution;

[0008] Wherein, the nickel salt is nickel nitrate hexahydrate, nickel chloride hexahydrate, nickel sulfate, nickel acetate or any combination thereof; the iron salt is ferric nitrate nonahydrate, ferric chloride hexahydrate, ferric sulfate, ferric acetate or any combination thereof; the volume ratio of the total mole of the nickel salt and the iron salt to the first mixed solution is 1:151 mmol / mL to 1:102 mmol / mL; the volume ratio of the isopropanol, glycerol and deionized water in the first mixed solution is 45:5:1 to 60:7.5:3;

[0009] Step 2: pour the second mixed solution into the polytetrafluoroethylene liner and continue stirring for 30 to 60 minutes;

[0010] Step 3: Transfer the polytetrafluoroethylene liner to a high-pressure reactor, react at 200° C. for 12 hours, and then cool to room temperature to obtain a nickel-iron metal alkoxide catalyst.

[0011] Preferably, the molar ratio of the nickel salt to the iron salt is 1:3 to 3:1.

[0012] Preferably, the molar ratio of the nickel salt to the iron salt is 1:3, 1:1 or 3:1.

[0013] Furthermore, the preparation method further comprises step 4: washing the nickel-iron metal alkoxide catalyst with anhydrous ethanol for multiple times and then drying it, preferably in an oven at 60° C. for 24 hours.

[0014] Preferably, the nickel salt is nickel nitrate hexahydrate, and the iron salt is iron nitrate nonahydrate.

[0015] Preferably, the nickel salt is nickel chloride hexahydrate, and the iron salt is ferric chloride hexahydrate.

[0016] Preferably, the nickel salt is nickel sulfate, and the iron salt is iron sulfate.

[0017] Preferably, the nickel salt is nickel acetate, and the iron salt is iron acetate.

[0018] Preferably, the stirring is magnetic rotor stirring, and the rotation speed is preferably 600 rpm to 1000 rpm.

[0019] The present invention also provides a nickel-iron-based metal alkoxide catalyst prepared by the above preparation method.

[0020] The present invention also provides an application of the nickel-iron-based metal alkoxide catalyst in an oxygen evolution reaction.

[0021] The present invention has at least the following technical effects:

[0022] 1. The present invention provides a controllable method for preparing nickel-iron-based metal alkoxides, which can realize the preparation of nickel-iron-based metal alkoxide catalysts with nanoscale regular and uniform morphology with different types of raw materials and different nickel-iron element ratios under the preparation condition of a hydrothermal reaction at 200°C for 12 hours, thereby laying a foundation for the application of nickel-iron-based metal alkoxide catalysts in oxygen evolution reaction (OER) catalysis.

[0023] 2. The nickel-iron-based metal alkoxide obtained by the preparation method of the present invention has an amorphous structure, which can expose more active sites and is more conducive to mass transfer. 2 The overpotential can be reduced to 215mV, which has excellent OER catalytic performance and can greatly reduce the energy consumption in the process of hydrogen production by water electrolysis.

[0024] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is an X-ray diffraction pattern of a nickel-iron-based metal alkoxide according to a preferred embodiment of the present invention;

[0026] Figure 2 is an FTIR graph of a nickel-iron-based metal alkoxide according to a preferred embodiment of the present invention;

[0027] Figure 3 The scanning electron microscope image (left figure) and the transmission electron microscope image (right figure) of a nickel-iron-based metal alkoxide of a preferred embodiment of the present invention are shown;

[0028] Figure 4 The oxygen evolution reaction curve of a nickel-iron-based metal alkoxide and commercial iridium dioxide measured in 0.1 mol / L KOH in a preferred embodiment of the present invention;

[0029] Figure 5 This is a stability test diagram of a nickel-iron-based metal alkoxide in 0.1 mol / L KOH according to a preferred embodiment of the present invention;

[0030] Figure 6 is a scanning electron microscope image of the nickel-iron-based metal alkoxide of Comparative Example 3;

[0031] Figure 7 is a scanning electron microscope image of the nickel-iron-based metal alkoxide of Comparative Example 4;

[0032] Figure 8 This is a scanning electron microscope image of the nickel-iron-based metal alkoxide of Comparative Example 5. DETAILED DESCRIPTION

[0033] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.

[0034] Embodiment 1:

[0035] 0.375 mmol of nickel nitrate hexahydrate and 0.125 mmol of ferric nitrate nonahydrate were uniformly dissolved in a mixed solution of 52.5 ml of isopropanol, 7.5 ml of glycerol and 1 ml of deionized water, and a magnetic rotor was added for stirring. After the solution was stirred until it dissolved to form a uniform dispersion, it was poured into a 100 ml polytetrafluoroethylene liner and stirred continuously at 800 rpm for about 40 minutes. The polytetrafluoroethylene liner was transferred to a stainless steel autoclave, and the autoclave was reacted at 200°C for 12 hours. After cooling to room temperature, the obtained nickel-iron-based metal alkoxide was washed five times with anhydrous ethanol and dried in an oven at 60°C for 24 hours.

[0036] Figure 1 is the X-ray diffraction pattern of nickel-iron-based metal alkoxide, Figure 2 This is the FTIR graph of nickel-iron-based metal alkoxide. Figure 3 The scanning electron microscope image (left) and transmission electron microscope image (right) of nickel-iron-based metal alkoxide. Figure 1-Figure 3 It can be seen that the obtained nickel-iron-based metal alkoxide has a regular and uniform spherical morphology and is free of other impurities.

[0037] Oxygen evolution reaction activity test:

[0038] Weigh 2.5 mg of the nickel-iron-based metal alkoxide catalyst obtained in Example 1, 1 mg of nano-carbon powder material, and 10 μl of Nafion and dissolve them in a mixed solution of 740 μl of deionized water and 250 μl of anhydrous ethanol. Ultrasonicate for 1 hour, take 10 μl of the slurry and drop it on a glassy carbon electrode with a diameter of 4 mm, and dry it at room temperature for 30 minutes.

[0039] 0.1 mol / L KOH was used as the electrolyte for the oxygen evolution reaction, and oxygen was passed through for 30 minutes before the test to ensure that the solution was saturated with oxygen. The test system was a three-electrode system, the working electrode was a glassy carbon electrode loaded with a nickel-iron-based metal alkoxide catalyst, a platinum sheet with a purity better than 99.99% was used as the counter electrode, and Hg / HgO was used as the reference electrode. The electrochemical workstation used for the test was the Shanghai Chenhua CHI 760e electrochemical workstation, with a scan speed of 5mV / s.

[0040] Figure 4 The oxygen evolution reaction curve of the nickel-iron-based metal alkoxide in Example 1 in 0.1 mol / L KOH is shown. 2When , the overpotential of nickel-iron metal alkoxide is 215mV. Figure 4 The oxygen evolution reaction curve of commercial iridium dioxide in 0.1 mol / L KOH is also shown. 2 The overpotential of commercial iridium dioxide is 324 mV. It can be seen that the catalytic performance of the nickel-iron-based metal alkoxide prepared by the present invention in the oxygen evolution reaction is much better than that of commercial iridium dioxide.

[0041] Figure 5 The stability test diagram of nickel-iron-based metal alkoxide in 0.1 mol / L KOH is shown. It can be seen that at a current density of 10 mA / cm 2 The electrolysis reaction can run stably.

[0042] Embodiment 2:

[0043] 0.25mmol of nickel nitrate hexahydrate and 0.25mmol of ferric nitrate nonahydrate were uniformly dissolved in a mixed solution of 45ml of isopropanol, 5ml of glycerol and 1ml of deionized water, and a magnetic rotor was added for stirring. After the solution was stirred until it dissolved to form a uniform dispersion, it was poured into a 100ml polytetrafluoroethylene liner and stirred at a speed of 600rpm for about 60 minutes. The polytetrafluoroethylene liner was transferred to a stainless steel autoclave, and the autoclave was reacted at 200°C for 12 hours. After cooling to room temperature, the obtained nickel-iron-based metal alkoxide was washed five times with anhydrous ethanol and dried in an oven at 60°C for 24 hours. The obtained nickel-iron-based metal alkoxide had a regular and uniform spherical morphology and no other impurities.

[0044] Embodiment 3:

[0045] 0.125mmol of nickel nitrate hexahydrate and 0.375mmol of ferric nitrate nonahydrate were uniformly dissolved in a mixed solution of 60ml of isopropanol, 7.5ml of glycerol and 3ml of deionized water, and a magnetic rotor was added for stirring. After the solution was stirred until it dissolved to form a uniform dispersion, it was poured into a 100ml polytetrafluoroethylene liner and stirred at a speed of 1000rpm for about 60 minutes. The polytetrafluoroethylene liner was transferred to a stainless steel autoclave, and the autoclave was reacted at 200°C for 12 hours. After cooling to room temperature, the obtained nickel-iron-based metal alkoxide was washed five times with anhydrous ethanol and dried in an oven at 60°C for 24 hours. The obtained nickel-iron-based metal alkoxide had a regular and uniform spherical morphology and no other impurities.

[0046] Embodiment 4:

[0047] 0.375 mmol of nickel chloride hexahydrate and 0.125 mmol of ferric chloride hexahydrate are uniformly dissolved in a mixed solution of 50 ml of isopropanol, 7.5 ml of glycerol and 1 ml of deionized water, and a magnetic rotor is added for stirring. After the solution is stirred until it is dissolved to form a uniform dispersion, it is poured into a 100 ml polytetrafluoroethylene liner and stirred at a speed of 800 rpm for about 30 minutes. The polytetrafluoroethylene liner is transferred to a stainless steel autoclave, and the autoclave is reacted at 200°C for 12 hours. After cooling to room temperature, the obtained nickel-iron metal alkoxide is washed five times with anhydrous ethanol and dried in an oven at 60°C for 24 hours. The obtained nickel-iron-based metal alkoxide has a regular and uniform spherical morphology and is free of other impurities.

[0048] Embodiment 5:

[0049] 0.375 mmol of nickel sulfate and 0.125 mmol of iron sulfate were uniformly dissolved in a mixed solution of 52.5 ml of isopropanol, 7.5 ml of glycerol and 1 ml of deionized water, and a magnetic rotor was added for stirring. After the solution was stirred until it dissolved to form a uniform dispersion, it was poured into a 100 ml polytetrafluoroethylene liner and stirred at 800 rpm for about 40 minutes. The polytetrafluoroethylene liner was transferred to a stainless steel autoclave, and the autoclave was reacted at 200°C for 12 hours. After cooling to room temperature, the obtained nickel-iron-based metal alkoxide was washed five times with anhydrous ethanol and dried in an oven at 60°C for 24 hours. The obtained nickel-iron-based metal alkoxide had a regular and uniform spherical morphology and no other impurities.

[0050] Embodiment 6:

[0051] 0.375 mmol of nickel acetate and 0.125 mmol of ferric acetate are uniformly dissolved in a mixed solution of 60 ml of isopropanol, 7.5 ml of glycerol and 1 ml of deionized water, and a magnetic rotor is added for stirring. After the solution is stirred until it is dissolved to form a uniform dispersion, it is poured into a 100 ml polytetrafluoroethylene liner and stirred at 800 rpm for about 40 minutes. The polytetrafluoroethylene liner is transferred to a stainless steel autoclave, and the autoclave is reacted at 200°C for 12 hours. After cooling to room temperature, the obtained nickel-iron metal alkoxide is washed five times with anhydrous ethanol and dried in an oven at 60°C for 24 hours. The obtained nickel-iron-based metal alkoxide has a regular and uniform spherical morphology and is free of other impurities.

[0052] Comparative Example 1:

[0053] Omit the iron nitrate nine hydrate in Example 1, replace 0.375mmol of nickel nitrate hexahydrate with 0.5mmol of nickel nitrate hexahydrate, and evenly dissolve it in a mixed solution of 52.5ml of isopropanol, 7.5ml of glycerol and 1ml of deionized water, add a magnetic rotor for stirring, stir the solution until it is dissolved to form a uniform dispersion, pour it into a 100ml polytetrafluoroethylene liner, and continue stirring at a speed of 800rpm for about 40 minutes. Transfer the polytetrafluoroethylene liner to a stainless steel autoclave, react the autoclave at 200℃ for 12 hours, cool it to room temperature, and then wash the obtained nickel-based metal alkoxide with anhydrous ethanol five times and dry it in an oven at 60℃ for 24 hours.

[0054] The same oxygen evolution reaction activity test as in Example 1 was carried out. The nickel-based metal alkoxide in Comparative Example 1 was tested at a current density of 10 mA / cm 2 The overpotential obtained when the current density is 10mA / cm 2 The overpotential at 215 mV is 215 mV. The overpotential of the nickel-based metal alkoxide in Comparative Example 1 is higher than that of the nickel-iron-based metal alkoxide in Example 1, and its catalytic performance in oxygen evolution reaction is weaker than that of the nickel-iron-based metal alkoxide.

[0055] Comparative Example 2:

[0056] Omit the nickel nitrate hexahydrate in Example 1, replace 0.125mmol of ferric nitrate nonahydrate with 0.5mmol of ferric nitrate nonahydrate, and evenly dissolve it in a mixed solution of 52.5ml of isopropanol, 7.5ml of glycerol and 1ml of deionized water, add a magnetic rotor for stirring, stir the solution until it is dissolved to form a uniform dispersion, pour it into a 100ml polytetrafluoroethylene liner, and continue stirring at a speed of 800rpm for about 40 minutes. Transfer the polytetrafluoroethylene liner to a stainless steel autoclave, react the autoclave at 200°C for 12 hours, cool it to room temperature, and then wash the obtained iron-based metal alkoxide with anhydrous ethanol five times and dry it in an oven at 60°C for 24 hours.

[0057] The same oxygen evolution reaction activity test as in Example 1 was carried out. The iron-based metal alkoxide in Comparative Example 2 was tested at a current density of 10 mA / cm 2 The overpotential obtained when the current density is 10mA / cm 2 The overpotential at 215 mV is 215 mV. The overpotential of the iron-based metal alkoxide in Comparative Example 2 is higher than that of the nickel-iron-based metal alkoxide in Example 1, and its catalytic performance in the oxygen evolution reaction is weaker than that of the nickel-iron-based metal alkoxide.

[0058] Comparative Example 3:

[0059] 0.375 mmol of nickel nitrate hexahydrate and 0.125 mmol of ferric nitrate nonahydrate were uniformly dissolved in a mixed solution of 52.5 ml of isopropanol and 7.5 ml of glycerol, and a magnetic rotor was added for stirring. After the solution was stirred until it dissolved to form a uniform dispersion, it was poured into a 100 ml polytetrafluoroethylene liner and stirred at 800 rpm for about 40 minutes. The polytetrafluoroethylene liner was transferred to a stainless steel autoclave, and the autoclave was reacted at 180°C for 6 hours. After cooling to room temperature, the obtained nickel-iron-based metal alkoxide was washed five times with anhydrous ethanol and dried in an oven at 60°C for 24 hours.

[0060] Comparative Example 3: 1 ml of deionized water in Example 1 was omitted, and the reaction at 200°C for 12 hours in the autoclave was replaced by the reaction at 180°C for 6 hours. Other conditions or parameters were the same as those in Example 1. The morphology of the nickel-iron-based metal alkoxide was obtained as follows: Figure 6 As shown, its morphology is irregular and uniform and contains fine impurities.

[0061] Comparative Example 4:

[0062] 0.375 mmol of nickel nitrate hexahydrate and 0.125 mmol of ferric nitrate nonahydrate were uniformly dissolved in a mixed solution of 52.5 ml of isopropanol and 7.5 ml of glycerol, and a magnetic rotor was added for stirring. After the solution was stirred until it dissolved to form a uniform dispersion, it was poured into a 100 ml polytetrafluoroethylene liner and stirred at 800 rpm for about 40 minutes. The polytetrafluoroethylene liner was transferred to a stainless steel autoclave, and the autoclave was reacted at 200°C for 12 hours. After cooling to room temperature, the obtained nickel-iron-based metal alkoxide was washed five times with anhydrous ethanol and dried in an oven at 60°C for 24 hours.

[0063] Comparative Example 4 omitted 1 ml of deionized water in Example 1, and other conditions or parameters were consistent with Example 1. The morphology of the obtained nickel-iron-based metal alkoxide is as follows: Figure 7 As shown, its morphology is irregular and uniform and contains fine impurities.

[0064] Comparative Example 5:

[0065] 0.375 mmol of nickel nitrate hexahydrate and 0.125 mmol of ferric nitrate nonahydrate were uniformly dissolved in a mixed solution of 52.5 ml of isopropanol, 7.5 ml of glycerol and 1 ml of deionized water, and a magnetic rotor was added for stirring. After the solution was stirred until it dissolved to form a uniform dispersion, it was poured into a 100 ml polytetrafluoroethylene liner and stirred at 800 rpm for about 40 minutes. The polytetrafluoroethylene liner was transferred to a stainless steel autoclave, and the autoclave was reacted at 180°C for 6 hours. After cooling to room temperature, the obtained nickel-iron-based metal alkoxide was washed five times with anhydrous ethanol and dried in an oven at 60°C for 24 hours.

[0066] Comparative Example 5: The reaction at 200°C for 12 hours in Example 1 was replaced by the reaction at 180°C for 6 hours. Other conditions or parameters were the same as those in Example 1. The morphology of the obtained nickel-iron-based metal alkoxide was as follows: Figure 8 As shown, its morphology is irregular and uniform and contains fine impurities.

[0067] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing a nickel-iron-based metal alkoxide catalyst, characterized in that: The following steps are involved: Step 1, dissolving nickel salt and iron salt in a first mixed solution comprising isopropanol, glycerol and deionized water to obtain a second mixed solution; Wherein, the nickel salt is nickel nitrate hexahydrate, nickel chloride hexahydrate, nickel sulfate, nickel acetate or any combination thereof; the iron salt is ferric nitrate nonahydrate, ferric chloride hexahydrate, ferric sulfate, ferric acetate or any combination thereof; the volume ratio of the total mole of the nickel salt and the iron salt to the first mixed solution is 1:151 mmol / mL to 1:102 mmol / mL; the volume ratio of the isopropanol, glycerol and deionized water in the first mixed solution is 45:5:1 to 60:7.5:3; the molar ratio of the nickel salt to the iron salt is 1:3 to 3:1; Step 2: pour the second mixed solution into the polytetrafluoroethylene liner and continue stirring for 30 to 60 minutes; Step 3: Transfer the polytetrafluoroethylene liner to a high-pressure reactor, react at 200° C. for 12 hours, and then cool to room temperature to obtain a nickel-iron metal alkoxide catalyst.

2. The preparation method according to claim 1, characterized in that The molar ratio of the nickel salt to the iron salt is 1:3, 1:1 or 3:

1.

3. The preparation method according to claim 1, characterized in that: The preparation method further comprises step 4: washing the nickel-iron metal alkoxide catalyst with anhydrous ethanol for multiple times and then drying it.

4. The preparation method according to claim 1, characterized in that: The nickel salt is nickel nitrate hexahydrate, and the iron salt is iron nitrate nonahydrate.

5. The preparation method according to claim 1, characterized in that: The nickel salt is nickel chloride hexahydrate, and the iron salt is ferric chloride hexahydrate.

6. The preparation method according to claim 1, characterized in that: The nickel salt is nickel sulfate, and the iron salt is iron sulfate.

7. The preparation method according to claim 1, characterized in that: The nickel salt is nickel acetate, and the iron salt is iron acetate.

8. A nickel-iron-based metal alkoxide catalyst obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the nickel-iron-based metal alkoxide catalyst as claimed in claim 8 in oxygen evolution reaction.

Citation Information

Patent Citations

  • Preparation method of hollow microsphere structure catalyst

    CN112007645A